After Hegemony. - HATHAWAY, OONA A.; SHAPIRO, SCOTT J. (Foreign Policy)
The article focuses on the U.S. President Donald Trump announced that he was halting funding to the World Health Organization (WHO), delivering a major blow to an organization that depends on the U.S. for nearly 10 percent of its budget. It mentions the coronavirus pandemic has laid bare how much global institutions have come to rely on a U.S. that has now abdicated its role as the world's indispensable nation. It also mentions the international community needs rules for the regulation of computer hacking, but Russia, China, and the U.S. have been unable to agree on the rules or how to enforce them.